Pragmatic Analysis on Social Media (YouTube): Perlocutionary Speech Acts in Digital Communication in the Modern Era - Abdul Kadir Kesi (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study analyzes perlocutionary speech acts in digital communication on social media, especially YouTube, from a pragmatics perspective. In the modern era, YouTube serves as a dynamic platform where users engage in discussions related to political, social, and cultural issues. The focus of this research is on the comments on Rocky Gerung's YouTube content entitled Prabowo signals to keep Jokowi's Ministers in his cabinet. A tactic to please Jokowi temporarily, which often triggers interesting interactions in terms of support and criticism of the content. This research uses a qualitative approach with descriptive methods to categorize and analyze perlocutionary speech acts, namely how utterances affect the audience or encourage certain responses. Data were collected from several comments taken randomly from related videos, paying attention to how the utterances in the comments shape interactions and influence the views and emotional reactions or behavior of the audience. The results show that perlocutionary speech acts often appear in the form of expressions of support, criticism, and other emotional expressions. Comments such as “Disband Mulyono's Cabinet, arrest, prosecute, then make a new cabinet,” reflect strong emotional reactions and a desire for social change. In addition, comments supporting or rejecting Rocky Gerung's views show that these digital platforms play an important role in shaping public opinion. This research shows that communication on social media, particularly YouTube, is not only a tool for exchanging information, but also a tool that can influence social interaction and build public opinion. The findings provide deep insights into the dynamics of speech acts in digital communication and their relevance in understanding the changing ways of communicating in the modern era.